Explore the profile of students reading comprehensions proficiency in the universities of the KSA - Masoud Alotaibi, Nasser; Abdul Malik Mohamed Ismail, Shaik (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the study is to investigate the profile of university students reading comprehension proficiency in Saudi Arabia based on the benchmarking. To achieve this objective, the data was collected from the English students who were studying in the Saudi Arabian universities by using a purposive sampling technique. The research design consisted of both quantitative and qualitative approaches. The analysis of the study was done based on both perspectives, namely, descriptive and inferential. The key findings have shown that the mean score of the female as compared to the male is higher in the universities of Saudi Arabia, which shows that the female is higher as compared to the male in the Saudi Arabian universities. Based on the findings of the study, the current study contributed a body of literature that could become valuable for future research. The current study also contributed a finding that could provide a guideline to the universities, educators, and policymakers to know about the importance of English in Saudi Arabian universities and for other Arab universities. The research limitations and future directions are also discussed at the end of the study.